Factors associated with non-persistence to oral and inhaled antiviral therapies for seasonal influenza: a secondary analysis of a double-blind, multicentre, randomised clinical trial. Issue 7 (10th July 2017) - Flicoteaux, Remi; Protopopescu, Camelia; Tibi, Annick; Blanchon, Thierry; Werf, Sylvie Van Der; Duval, Xavier; Mosnier, Anne; Charlois-Ou, Cécile; Lina, Bruno; Leport, Catherine; Chevret, Sylvie
Abstract : Objectives: We aimed to evaluate and compare non-adherence to oral and inhaled antiviral therapies prescribed of a randomised clinical trial in outpatients with influenza A infection. Design: A parallel, three-arm, double-blinded trial randomly allocated antiviral therapies twice daily for 5 days: (1) oral oseltamivir plus inhaled zanamivir (arm OZ); (2) oseltamivir plus inhaled placebo (arm Opz); or (3) oral placebo plus inhaled zanamivir (arm poZ). Analysis of non-adherence was a secondary objective of the trial. Settings: Outpatients were enrolled by 145 general practitioners throughout France during the 2008–2009 seasonal influenza epidemics. Participants: A total of 541 adults presenting with influenza-like illness for less than 36 hours. Primary outcomes: Non-persistence, the time between inclusion and the last dose treated as a failure time, was used as the primary endpoint. Results: The proportions of patients who persisted on treatment until the end of prescription were estimated at 85.73% (±3.28%) for the oral route and 82.73% (±3.44%) for the inhaled route. Based on multivariable models, non-persistence was associated with a PCR confirmation of influenza for both the oral (HR=0.54, p=0.010) and inhaled (HR=0.59, p=0.018) drugs and antibiotic coprescriptions (HR=2.07, p=0.007; and HR=1.88, p=0.017, respectively) and active combination treatment (HR=1.71, p=0.035; and HR=1.58, p=0.035, respectively). The hazard of non-persistence of the inhaled therapy was increased compared with that of the oral therapy (HR=1.23, p=0.043). Conclusion: In addition to the clinical and virological profiles of influenza infection, non-persistence may have been influenced by an active combination and the route of administration. RCT registration number: NCT00799760. This is a post-result analysis.